Training may reduce knee injuries for female athletes
British Columbia-Female high school athletes who participated in a six-week preseason neuromuscular training program suffered serious knee injuries 72% less often than untrained female athletes, concluded a study presented at the annual meeting of the American Orthopaedic Society for Sports Medicine (AOSSM). "Our recommendation is that prior to participation, females should be tested for landing technique and hamstrings and quadriceps strength, and those with excessive varus/valgus landings or low hamstring-to-quadriceps ratios should be trained," said Timothy E. Hewett, PhD, of the Cincinnati Sportsmedicine and Orthopaedic Center. Although its results were intriguing, the study was not without limitations, Elizabeth A. Arendt, MD, said in discussing the work after its presentation. Arendt, an associate professor of orthopedic surgery at the University of Minnesota, cited the small number of serious knee injuries involved, how volunteers were distributed in the study and the lack of objective measurements taken before and after the six-week program. Despite those shortcomings-which Hewett acknowledged-Arendt praised the research, calling it an "ambitious" project that was a "landmark." If the results hold up, Hewett's research will be of great value to orthopedic surgeons specializing in sports medicine, coaches, team trainers and athletes, especially females.